GSTT1null and rs156697 Polymorphism in GSTO2 Influence the Risk and Therapeutic Outcome of B-Acute Lymphoblastic Leukemia Patients - Baba, Shahid M.; Pandith, Arshad A.; Shah, Zafar A.; Geelani, Sajad A.; Bhat, Javid R.; Gul, Ayaz; Guru, Sameer A.; El-Serehy, Hamed A.; Koul, Abid M.; Mansoor, Sheikh (Frontiers in Oncology, 2021)
Introduction: Glutathione S-transferase (GST) gene deletion or polymorphic sequence variations lead to decreased enzyme activity that influences susceptibility and response to chemotherapy in Acute Lymphoblastic leukemia (ALL). This case-control study investigated the association of GST gene polymorphisms with the etiology and therapeutic outcome of B-ALL among Kashmiri population. Methods: A total of 300 individuals including 150 newly diagnosed B-ALL patients and an equal number of age and gender matched controls were genotyped for five GST gene polymorphisms by Polymerase Chain Reaction-Restriction Fragment Length Polymorphism technique (PCR-RFLP) and multiplex PCR techniques. Results: Higher frequency of GSTT1null, GSTO2-AG and GSTO2-GG genotypes was observed in ALL cases compared to controls that associated significantly with ALL risk (GSTT1null: OR=3.52.93, p<=0.0001; GSTO2-AG: OR=1.872.48, p=0.01; GSTO2-GG: OR=2.643.13, p=0.01). GSTM1, GSTP1 and GSTO1 SNPs showed no significant association (p>0.05). Combined genotype analysis revealed significant association of GSTT1null/GSTM1null (OR=4.11, p= 0.011) and GSTT1null/GSTP1-AG (OR=4.93, p=0.0003) with B-ALL susceptibility. Haplotype analysis of rs4925 and rs156697 revealed that carriers of CG haplotype had an risk of B-ALL (p=0.04). Kaplan Meier plots revealed significantly inferior 3-year disease free survival for GSTO2-GG carriers (p=0.002). Multivariate analysis confirmed GSTO2-GG as an independent poor prognostic factor for DFS (HR=4.5, p=0.034). Among combined genotypes, only GSTT1null/GSTP1-AG associated significantly with poorer DFS rates (p=0.032). Conclusion: This study demonstrated that GSTT1null individually or in combination with GSTM1null and GSTP1-AG genotypes associated with increased B-ALL risk. Also, rs156697 variant genotypes (AG & GG) associated with B-ALL, whereas GG genotype of rs156697 influenced the treatment outcome.